Continuous innovation: towards a paradoxical, ambidextrous combination of exploration and exploitation. (1st January 2013) - Martini, Antonella; Laugen, Bjørge Timenes; Gastaldi, Luca; Corso, Mariano
The Continuous Innovation Network (CINet) is a global network studying the innovation processes through which the synergistic combination between exploratory and exploitatory activities fosters a synergistic combination of operational effectiveness and strategic flexibility – allowing firms to achieve superior performance. This paper presents the theoretical field of continuous innovation as an extension of the intersection of three research streams – namely exploration-exploitation, organisational ambidexterity and paradoxical thinking. Moreover, it presents four papers from the International CINet Conference held in Zürich (CH), from the 5th to the 7th of September 2010.